Progressive upper-body resistance training improves straight punch frequency-speed (punches per 10 s) in pencak silat athletes: a four-week pretest-posttest study - Rifqi Ahsan Rendra; Eval - Edmizal; Umar Umar; Juanda Putra (Journal of Educational and Learning Studies, 2026)
This study examined whether a four-week progressive upper-body resistance training program improves straight punch frequency-speed in club-level pencak silat athletes, for whom sport-specific upper-limb training evidence is scarce. A one-group pretest-posttest quasi-experimental design was used. Twelve athletes (aged 14 years or over, at least one year of training experience, injury-free) were purposively selected from 65 active club members in Padang, Indonesia. Participants completed 16 supervised sessions (four per week for four weeks) combining progressively loaded bench press, shoulder press and triceps extension (60% to 75-80% 1RM) with explosive transfer work (explosive push-ups, medicine-ball chest passes and throws, plyometric push-ups). The outcome measure was the number of legal straight punches delivered to a bag in a maximal 10 s effort, scored by the same rater under an identical protocol at both time points. Both distributions were normal (Shapiro-Wilk p = 0.561 and p = 0.190) and were analysed with a paired-samples t test (α = 0.05). Punch frequency rose from 46.33 ± 5.84 to 54.00 ± 3.52 punches/10 s, a mean gain of 7.67 punches (16.6%; 95% CI 5.25 to 10.08), t(11) = 6.99, p < 0.001, Cohen's dz = 2.02 (95% CI 1.00 to 3.01); between-athlete variability also fell significantly (Pitman-Morgan t(10) = 2.67, p = 0.024). Progressively loaded upper-body training with explosive transfer work therefore appears to be a practical, low-cost way of raising punch frequency-speed in pencak silat, most plausibly through early neural adaptation. Because the design was uncontrolled and the sample small, these findings are preliminary and require confirmation in randomised controlled trials.